Sufism, Orthodoxy, and Nationalism in Modern Islamic Civilization in North Africa from The 19th- 20th Century - Dudung Abdurahman; Kholili Badriza (Sunan Kalijaga: International Journal of Islamic Civilization, 2021)
The phenomenon of Sufism in the tariqa movements played a significant role in Islamic reform and the growth of nationalism in North Africa from the 19th to 20th centuries. This phenomenon which started as a neo-Sufism for Islamic reform, gradually turned into a nationalist movement. Therefore, Sufism is assumed to be a part of Islam that occupies the basic component of national identity and is a symbol of the struggle for independence of Muslim countries in North Africa. This study aims to discuss "the role and influence of Sufism for the revival of Islam, resistance to Western colonialism, the role of Islamic reform, and the process of nationalism and independence of Muslim countries in North Africa." These problems are analyzed based on historical, social, and political approaches related to issues of modern civilization in the Islamic world. This research concludes that, firstly the Sufism movement in the modern period in North Africa is developed in tariqa schools located in Idrisiyah, Sanusiyah, Khatmiyah, Tijaniyah, Qadiriyah, and Sammaniyah. Furthermore, the Sufism movement always shows the intertwined elements of teachings and rituals as well as the influences of social and political developments. Secondly, the teachings of the tariqa are able to increase religious awareness by fulfilling spirituality and improving people's morality, thereby developing, modifying, and actualizing leadership associated with Sufis. Thirdly, Sufism shows a very significant social force regarding the growth of nationalism in North Africa, which is used as the basis for their participation in the socio-political field, with various forms of protest or resistance. In collaboration with religious and community leaders, the leadership of the Sufis has also succeeded in bringing about the independence of national countries such as Tunisia, Libya, Algeria, Morocco, and Sudan since the mid-20th century. During that time, many Sufists occupied important positions in government.